Clinical Spectrum of Cutaneous Malignancies in Nepal: A Retrospective Cross-Sectional Study at Dhulikhel Hospital - Shrestha, Elisha; Tamang, Ashish; Karn, Dharmendra; Basukala, Manisha Singh; Mishra, Aditi; Shrestha, Binaya; Basnet, Aniket; Regmi , Bidhi (Journal of Nobel Medical College, 2025)
Background: Skin cancer epidemiology varies by geography and ethnicity. While basal cell carcinoma predominates globally, squamous cell carcinoma may be more common in high-ultraviolet (UV) regions with darker-skinned populations.Materials and Methods: A 5-year retrospective cross-sectional study (2019-2023) of histologically confirmed skin cancers at Dhulikhel Hospital, Nepal. Data on demographics, histology, tumor sites, and risk factors were analyzed. Pearson correlation assessed the sun exposure association.Results: A total of 140 patients were included. The mean age was 60.04 ± 18.04 years, with 57.1% aged over 60. Males comprised 55% and women 45% (M:F ratio = 1.2:1). Squamous cell carcinoma was the most common skin cancer (52.9%), followed by basal cell carcinoma (42.1%) and melanoma (5%). The head and neck was the most frequently affected site. A history of prolonged sun exposure was present in 75.7% of patients, and a statistically significant correlation was found between sun exposure and skin cancer (Pearson correlation = 0.191, p = 0.024). Six patients had xerodermapigmentosum.Conclusion: Squamous cell carcinoma predominates in Dhulikhel Hospital, Kavre, contrasting global Basal cell carcinoma (BCC) trends. Elderly males with high sun exposure are most affected, highlighting ultraviolet(UV) radiation's role.